Plastics: Friend or foe? - O P Gupta (Journal of Mahatma Gandhi Institute of Medical Sciences, 2018)
Plastics has been playing a very significant role in our life. Being light weight, inexpensive and heving good insulating properties it is being used in all aspects of life, from clothes to contact lenses and from mobile phones to automobiles as well as in medical equipments, However it is not biodegradable, and while degrading to fragments it gets converted in to microplastics and nanoplastics The plastic waste is being recognized as an environmental hazard, since these micr- and nanoplastics find way from landfills to water and foods, It is said that we are not only using, but we are eating, drinking and even braething the plastics. These microplastics in body release certain hazardous chemicals and found to be disrupting functions of certain endocrine organs. Whether the rising prevalence of Diabetes, thyroid disorders or infirtility etc., are realated to the plastics?